Criminological Characteristics of Migrant Crimes: Russian and Foreign Practices - Kabanov, Pavel; Khairutdinova, Liliya; Bulanova, Leisan (International Journal of Criminology and Sociology, 2022)
Migrants and ever-rising incidences of immigrant crimes tend to be perceived as a serious threat provoking fear and apprehension throughout the world. The current study provides useful insights into immigrant criminality and the ways of its deterrence. However, despite all recent attempts to carry out the scientific assessment of criminological characteristics of the studied social and legal phenomenon there is a strong need for a comprehensive study of foreign scientific literature and practice.